PERKEMBANGAN KEBIJAKAN INDUSTRI PERTAHANAN INDONESIA - Avira Durrotul Rasyida; I Nengah Putra Apriyanto; George Royke Deksino (DAS Institute, 2022)
Basis regulation of Indonesia's defense industry is Law No. 16 of 2012. This regulation is supported by Presidential Regulation No. 59 of 2013, Government Regulation No. 141 of 2015, which details defense industry policies in Indonesia. The Omnibus Law 2020 provides changes to several articles of Law No. 16 of 2012. Therefore, it is necessary to study and analyze the development of defense industry policies and changes to the legal basis of the defense industry. This study uses a descriptive-analytical method with a juridical approach to analyze secondary data in legal aspects. Analytical descriptive collects data through literature studies, documents, and archive studies. Based on this research, the defense industry policy in Indonesia has developed from time to time, as well as changes in the basic regulation in several aspects of Law No. 16 of 2012 with the Omnibus Law 2020. Developments and changes are carried out in order to realize the independence of the national defense industry. Changes in the regulations of several articles related to business licensing for private participation in competing in the production of main equipment and capital ownership and reducing the authority of the KKIP (Defense Industry Policy Committee)